Melusin Promotes a Protective Signal Transduction Cascade in Stressed Hearts - Sorge, Matteo; Brancaccio, Mara (Frontiers in Molecular Biosciences, 2016)
Melusin is a chaperone protein selectively expressed in heart and skeletal muscles. Melusin expression levels correlate with cardiac function in pre-clinical models and in human patients with aortic stenosis. Indeed, previous studies in several animal models indicated that Melusin plays a broad cardioprotective role in different pathological conditions. Chaperone proteins, besides playing a role in protein folding, are also able to facilitate supramolecular complex formation and conformational changes due to activation/deactivation of signaling molecules. This role sets chaperone proteins as crucial regulators of intracellular signal transduction pathways. In particular Melusin activates AKT and ERK1/2 signaling, protects cardiomyocytes from apoptosis and induces a compensatory hypertrophic response in several pathological conditions. Therefore, selective delivery of Melusin gene in the heart via cardiotropic adenoviral associated virus serotype 9 (AAV9), may represent a new promising gene-therapy approach for different cardiac pathologies.